THE FUNCTION OF ASSERTIVE SPEECH ACTS IN THE NOVEL CALABAI BY PEPI AL-BAYQUNIE - Isnaeni Isnaeni; Mantasiah R.; Hasmawati Hasmawati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This research aims to analyze the function of assertive speech acts contained in the novel Calabai by Pepi Al-Bayqunie. Assertive speech act is a type of speech act that states something in accordance with reality, such as stating, informing, recommend, refuting, emphasizing, demanding, reporting, denying, disprove, hinting, boasting, complaining, and claiming. This study examines how the characters in the novel use assertive speech acts to express opinions, explain facts, and form social relations. The research is conducted by using pragmatic approach based on Searle's theory then the functions are mapped based on Leech's theory. The results show that the functions of assertive speech acts in this novel include cooperative functions, competitive functions, conflicting functions, and fun functions. These functions illustrate the social values and Bugis culture. Thus, the assertive speech acts in the novel Calabai not only function as a communication tool, but also as a means of conveying social criticism and strengthening identity.